2021
DOI: 10.1088/1361-6501/abd799
|View full text |Cite
|
Sign up to set email alerts
|

Traceability of network time service to UTC(NIM): online calibration

Abstract: Network time service provided by Network Time Protocol (NTP) servers is widely used to synchronize the clocks of computers and other networked equipment. With the rapid development of smart devices and their applications, more NTP servers as time sources need to be calibrated to a legal time reference. This work proposes using a low-cost and convenient calibration method to investigate the time service capability of ten NTP servers located at different cities in China. The uncertainties (k = 2) of the time off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Therefore, a timekeeping error of a hundred microseconds in an NTP system built over a LAN with a symmetrical path and no more than 2-3 interconnection elements between two NTP servers is considered optimum [11][12][13]. In contrast, for synchronization accuracy on a WAN a time error is, usually, below 10 ms in a 200-node WAN [14].…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Therefore, a timekeeping error of a hundred microseconds in an NTP system built over a LAN with a symmetrical path and no more than 2-3 interconnection elements between two NTP servers is considered optimum [11][12][13]. In contrast, for synchronization accuracy on a WAN a time error is, usually, below 10 ms in a 200-node WAN [14].…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Due to its self‐lubricating ability and chemical resistance, the use of polymer‐based composites is concentrated in the manufacture of machine elements such as bearings, bushings, thrusts, for which tribological performance is important. [ 1–7 ] From this perspective, a non‐flammable material with a melting point of 288°C, able to withstand high operating temperatures up to 200°C, chemically insoluble at temperatures below 200°C, corrosion resistant, non‐shrinking in the mold, exhibiting a tensile strength of around 70 MPa, poly(phenylene sulphide) (PPS) is a successful matrix material for use in many advanced engineering applications. [ 8–10 ]…”
Section: Introductionmentioning
confidence: 99%
“…In terms of modifying resin matrix, the research focused on mixing functionalized PPS into the primeval one. For example, Yang Jie et al blended aminated and carboxylated PPS with commercial PPS respectivelyto increase the reactivity of the resin matrix, resulting in effective chemical connection between the resin and the oxidatively modified carbon fibers, the test results showed that IFSS values increased from 30.4 and 36.1 MPa before treatment to 33.6 and 49.1 MPa, respectively 31,32 …”
Section: Introductionmentioning
confidence: 99%